2006
DOI: 10.1109/tbme.2005.862572
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Biased, Asymmetric Waveforms for Charge-Injection With Activated Iridium Oxide (AIROF) Neural Stimulation Electrodes

Abstract: The use of potential biasing and biphasic, asymmetric current pulse waveforms to maximize the charge-injection capacity of activated iridium oxide (AIROF) microelectrodes used for neural stimulation is described. The waveforms retain overall zero net charge for the biphasic pulse, but employ an asymmetry in the current and pulse widths of each phase, with the second phase delivered at a lower current density for a longer period of time than the leading phase. This strategy minimizes polarization of the AIROF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 23 publications
4
115
0
Order By: Relevance
“…6,10,30,33 Reported Coulombic charges for the capacitance of Ir oxide can further vary between 1 and several hundred mC cm Ir −2 based on the experiment type (faradaic or capacitive), medium, and deposition technique. [34][35][36][37][38] The mass-based capacitances found in this study on Ir oxide are comparable to those previously found in RDE half-cells and single-cell electrolyzers. 6,30 Capacitance has also been used to determine the ECA of Ir nanoparticles and baseline its activity in OER.…”
Section: Resultssupporting
confidence: 87%
“…6,10,30,33 Reported Coulombic charges for the capacitance of Ir oxide can further vary between 1 and several hundred mC cm Ir −2 based on the experiment type (faradaic or capacitive), medium, and deposition technique. [34][35][36][37][38] The mass-based capacitances found in this study on Ir oxide are comparable to those previously found in RDE half-cells and single-cell electrolyzers. 6,30 Capacitance has also been used to determine the ECA of Ir nanoparticles and baseline its activity in OER.…”
Section: Resultssupporting
confidence: 87%
“…This stimulation current corresponds to 10 nC injected per pulse and a maximum electrode charge density of 0.8 mC/cm 2 . Since this charge density exceeds the safe limit for platinum electrodes (0.4 mC/cm 2 [18,19]) we use activated iridium oxide film (AIROF) electrodes, which have a safe charge-injection limit of 1-9 mC/cm 2 [20].…”
Section: System Designmentioning
confidence: 99%
“…The large size of the electrodes has limited the density of electrodes that can be placed over a given area. The choice of electrode size has been dictated mostly by the potential for damage to the electrode and surrounding tissue posed by high charge densities [6,7]. Perceptual threshold measurements obtained in blind humans have varied widely, although 0.5 μC/phase is reasonably good representation of the collective results [8].…”
Section: Introductionmentioning
confidence: 99%